Understanding the impact of lifestyle and demographic factors on DNA fragmentation index (DFI) among infertile men - Abayomi Bolaji Ajayi; Victor Ajayi; Kazeem Adewale Osuolale; Ngozi Obi; Roselyn Obasa-Gbadebo; Toluwanimi Balogun; Anuoluwa Alaka; Olaoluwa Musa; Edith Omokhegbele (BMC Urology)
Abstract Background Sperm DNA fragmentation detection methods include SCSA, SCD, COMET assay, and TUNEL. In 2021, the DFI test became the first evidence-based sperm DNA integrity test included in international guidelines. However, limited data exists from Nigeria. This study explores the relationship between demographic, lifestyle, and medical factors and DFI among infertility patients at Nordica Fertility Centre, aiming to guide interventions to improve fertility outcomes. Methods A total of 643 male infertility patients undergoing DFI analysis were evaluated. Participants were categorized based on age, occupation, BMI, alcohol use, smoking habits, and ejaculation frequency. The DFI was assessed both continuously and categorically using a 25% threshold (≤ 25% good, > 25% poor integrity). Chi-square tests examined associations between categorical variables while t-test was also used to examine significant association in terms of mean comparisons between DFI and other variables. Logistic regression analysis, with forward stepwise selection, identified independent predictors of high DFI, adjusting for potential confounders. Results Participants had a mean age of 44.1 years; 55.7% were under 45. Most were professionals (57.1%) with a mean BMI of 27.5 kg/m². Alcohol use was reported by 45.2% and smoking by 9.6%. Mean DFI was 37.8% (range: 6–93%). Higher DFI was significantly associated with older age (χ²=12.21, p = 0.001), non-professional occupation (χ²=162.75, p < 0.001), and poor sperm motility (χ²=5.724, p = 0.017). Logistic regression showed that age above 45 years (OR = 2.45, 95% CI: 1.39–4.32, p = 0.002), occupation category (Professional/Technical/Managerial/ Clerical) (OR = 0.001, 95% CI: 0.0001–0.011, p < 0.001), and alcohol use (OR = 18.01, 95% CI: 7.03–46.12, p < 0.001) were independently associated with the outcome. Conclusion Older age, alcohol consumption, Professional/Technical/Managerial/ Clerical occupations, and alcohol use are associated with increased sperm DNA fragmentation. These findings highlight the need for personalized fertility assessments and targeted interventions to enhance male reproductive health.